Perception of quality in sport – qualitative and quantitative approach - Łasiński, Gabriel (Journal of Education, Health and Sport, 2017)
The main purpose of the article is to present a problem of quality in sport from the system (holistic) perspective and reveal its diversity, complexity and multidimensionality. The author presents an extensive review of different approaches and concepts of quality in the literature as well as methods of measurement in sport. The article is conceptual and demonstrates a model of quality, which was preceded by a literature review. The author describes a model of structural orders, indicates crucial sport areas and presents its different aspects of measurement quality in sport: dimensions, scales, criteria and measures. In this part, the praxeological approach (with effectiveness criteria) is distinguished and justified. In the next part of the article, the emotional (qualitative) and material (quanitative) dimensions of quality of sport spectacles are discussed as well as contemporary trends of those dimensions diffusion.